Development of Interactive E-Module Based on Inquiry Learning to Enhance IPAS Learning Outcomes for Students Public Elementary School - Ramadhani, Arum Ayu; Andriani, Aldina Eka (Jurnal Pijar Mipa, 2024)
The purpose of this study was to develop and test the feasibility and effectiveness of an Interactive E-Module based on Inquiry Learning teaching materials on improving the cognitive learning outcomes of IPAS for fourth-grade students of SD Negeri Tambahagung 03 Pati Regency. This type of development research is Research and Development (R&D) using the ADDIE development model. The novelty of this research is the development of material on the Human Sensory System in teacher books and student books based on an innovative learning model, namely Inquiry Learning, which includes interactive edugame evaluations. The results showed the feasibility of media experts with a score of 89.0635% in the very feasible category and material experts with a score of 91.23% in the very feasible category. This is supported by a teacher-response questionnaire of 97.5% and a student-response questionnaire of 93.73%. The effectiveness of Interactive E-Modules based on Inquiry Learning based on the cognitive learning outcomes of students has increased with a normality test analysis, which shows that pre-test and post-test data are typically distributed. The results of the T-test calculation show that there is a significant difference between the pre-test and post-test learning outcomes with the acquisition of a medium category average through the N-Gain test. The conclusion of the research on the development of inquiry learning-based interactive e-modules was successfully developed, and it was very feasible and effective for improving the cognitive learning outcomes of IPAS fourth-grade students of SD Negeri Tambahagung 03 Pati Regency.